3x+5y+11=4(5x-2y)

Simple and best practice solution for 3x+5y+11=4(5x-2y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5y+11=4(5x-2y) equation:


Simplifying
3x + 5y + 11 = 4(5x + -2y)

Reorder the terms:
11 + 3x + 5y = 4(5x + -2y)
11 + 3x + 5y = (5x * 4 + -2y * 4)
11 + 3x + 5y = (20x + -8y)

Solving
11 + 3x + 5y = 20x + -8y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
11 + 3x + -20x + 5y = 20x + -20x + -8y

Combine like terms: 3x + -20x = -17x
11 + -17x + 5y = 20x + -20x + -8y

Combine like terms: 20x + -20x = 0
11 + -17x + 5y = 0 + -8y
11 + -17x + 5y = -8y

Add '-11' to each side of the equation.
11 + -17x + -11 + 5y = -11 + -8y

Reorder the terms:
11 + -11 + -17x + 5y = -11 + -8y

Combine like terms: 11 + -11 = 0
0 + -17x + 5y = -11 + -8y
-17x + 5y = -11 + -8y

Add '-5y' to each side of the equation.
-17x + 5y + -5y = -11 + -8y + -5y

Combine like terms: 5y + -5y = 0
-17x + 0 = -11 + -8y + -5y
-17x = -11 + -8y + -5y

Combine like terms: -8y + -5y = -13y
-17x = -11 + -13y

Divide each side by '-17'.
x = 0.6470588235 + 0.7647058824y

Simplifying
x = 0.6470588235 + 0.7647058824y

See similar equations:

| 2x^2-3x=40 | | 13x=6x+42 | | x^6+x^2= | | 4x^2+5=20 | | x+(x+6)+2x=94 | | 6n+3=63 | | 5(3y-1)-1(2y)=10 | | x^2-37=0 | | -5x^2+10x=0 | | -3+n=-91 | | -2x=7y-19 | | -17=63+n | | 2+5*3+4= | | 35x^2+x-6=0 | | n+(-3)=-91 | | 7.32xA=13.53+2.81xA | | 9+2(x-7)=0 | | 2x+(3x+4)=4 | | 92=6+3w | | 92=6+1/2 | | 7x-4=2x+2 | | 92=2+6w | | 0x-.99-3x=-15 | | 92=6+2w | | 2a^2=196 | | 0.4x=8 | | 315=21s | | 15x^2=-3-14x | | 792=-33y | | 24+x^2=10x | | x-2x-1=x+1 | | 0.6+0.3x=0.8+0.4x |

Equations solver categories